1986
DOI: 10.1177/154193128603000812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Display Proximity and Memory Demands on the Understanding of Dynamic Multidimensional Information

Abstract: Two experiments explored the ability of individuals to integrate several sources of information about units or conceptual objects. The task domain might describe the air traffic controller's monitoring of the horizontal and vertical separation of several aircraft, the process controller's supervision of the temperature, pressure, and entropy of several energy systems, or any other multidimensional database. The first experiment examined working memory limits for different object-attribute combinations. When su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…At intermediate rates (1 letter every 2 to 3 s), the fastest stimulus on times optimized performance. Similar results were obtained by Harwood, Wickens, Kramer, Clay and Liu (1986) in a simulated air traffic control task. In the first experiment, people were required to remember the status of 2, 3, or 6 aircraft that were defined by 1-3 attributes that changed over time.…”
Section: Keeping Track Of Changes In Attributessupporting
confidence: 76%
See 1 more Smart Citation
“…At intermediate rates (1 letter every 2 to 3 s), the fastest stimulus on times optimized performance. Similar results were obtained by Harwood, Wickens, Kramer, Clay and Liu (1986) in a simulated air traffic control task. In the first experiment, people were required to remember the status of 2, 3, or 6 aircraft that were defined by 1-3 attributes that changed over time.…”
Section: Keeping Track Of Changes In Attributessupporting
confidence: 76%
“…There is considerable evidence to suggest, however, that an object-like representation of multidimensional data can enhance the detection and recognition of changes in state (Buttigieg and Sanderson, 1991;Carswell and Wickens, 1987;Sanderson, Flach, Buttigieg and Casey, 1989), especially when the display produces a unique mapping of perceptual cues to a state category (Coury and Boulette, 1992;Coury, Boulette and Smith, 1989). Although Harwood et al, (1986) used the spatial location of an aircraft as a location cue and color coding to indicate related attributes, the values of critical aircraft parameters (altitude, airspeed and heading) were presented digitally. Since many tactical displays represent the attributes of battlefield entities in a graphical format, none of these studies directly comment on the effect of graphical representations or the effectiveness of current tactical symbology on keeping track performance.…”
Section: Keeping Track Of Changes In Attributesmentioning
confidence: 99%
“…Previously, the proximity compatibility principle has been extensively tested in experimental paradigms in which bar graphs, triangles and rectangles are used to represent variables in hypothetical systems (see, e.g. Harwood, Wickens, Kramer, Clay & Liu, 1986). Those studies defined display proximity as the relation between separate dimensions of a stimuli, e.g., the height and the width of a rectangle.…”
Section: Discussionmentioning
confidence: 99%
“…Vincow and Wickens found that performance and spatial distance between information was negatively correlated if more information integration was required. Also, it was suggested that people recalled information better when presented with many attributes of a few objects (Harwood et al, 1986). Moreover, it was found that the layout of information significantly influenced human's performance.…”
Section: Information Layoutmentioning
confidence: 99%
“…Lok et al (2004) created a WeightMaps tool to analyze the visual weight of information presentation in order to evaluate the effectiveness of different information layouts. Moreover, it has been found that distance between stimuli was determined by the level of information integration (Harwood, Wickens, Kramer, Clay, & Liu, 1986;Vincow & Wickens, 1993). Vincow and Wickens found that performance and spatial distance between information was negatively correlated if more information integration was required.…”
Section: Information Layoutmentioning
confidence: 99%